Edukasi dan Pelatihan Pembuatan Serbuk Sari Buah Mengkudu (Morinda Citrifolia L.) Untuk Pengendalian Hipertensi - Asyikin, Asyhari; Nurisyah, Nurisyah (Jurnal Pengabdian Kefarmasian, 2025)
Education and Training on Producing Noni Fruit (Morinda citrifolia L.) For Hypertension ControlBackground Hypertension is a serious problem because one in three adults worldwide suffers from hypertension and is currently a trending urban health problem. In 2025, it is predicted that 29% of adults worldwide will suffer from hypertension. The proportion of hypertension in Indonesia has increased in 2018, which was 34.1%. Hypertension sufferers in Makassar City have increased every year. In 2020, the number of hypertension cases in Makassar City reached 40,288 cases. In overcoming the incidence of hypertension, some people in Pa'baeng-baeng Village, Tamalate District, Makassar City have never been exposed to counseling related to hypertension so that most of them check their blood pressure if they already have hypertension. The purpose of the activity is to provide counseling on hypertension, create a module on how to make instant herbal powder from noni fruit, red ginger, cinnamon, and cloves (MORIZYA instant powder) to control hypertension. Method This activity was carried out in the Pa'baeng-baeng Village area, Tamalate District, Makassar City. Tamalate Makassar City in the form of counseling and training on making instant herbal powder MORIZYA for controlling hypertension and to measure the success and effectiveness of education in this community service activity, an evaluation was carried out through a pre-test and post-test. The results of the activity showed that there were 30 people who participated in the activity and the results of the post-test showed that after the education, the participants' knowledge increased by 4.2 points (42%). The conclusion is that there is an increase in public knowledge about hypertension and they are able to make instant powder MORIZYA for controlling hypertensionLatar Belakang Hipertensi menjadi masalah serius karena satu dari tiga orang dewasa diseluruh dunia menderita hipertensi dan menjadi tren masalah kesehatan perkotaan saat ini. Pada tahun 2025, diprediksi 29% orang dewasa di seluruh dunia menderita hipertensi. Proporsi penyakit hipertensi di Indonesia semakin meningkat pada tahun 2018, yaitu 34,1%. Penderita hipertensi di Kota Makassar mengalami peningkatan setiap tahunnya. Pada tahun 2020 jumlah kasus hipertensi di Kota Makassar mencapai 40.288 kasus. Dalam penanggulangan kejadian penyakit hipertensi, sebagian masyarakat di Kelurahan Pa’baeng-baeng Kecamatan Tamalate Kota Makassar belum pernah terpapar penyuluhan terkait hipertensi sehingga kebanyakan dari mereka, memeriksakan tekanan darahnya apabila sudah mengalami hipertensi. Tujuan Kegiatan untuk melakukan penyuluhan tentang hipertensi, pembuatan modul tentang cara pembuatan serbuk instan herbal dari buah mengkudu, jahe merah, kayu manis, dan cengkeh (sebuk instan MORIZYA) untuk pengendalian hipertensi. Metode Kegiatan ini dilakukan di wilayah Kelurahan Pa’baeng-baeng Kec. Tamalate Kota Makassar dalam bentuk penyuluhan dan pelatihan pembuatan herbal serbuk instan MORIZYA untuk pengendalian Hipertensi dan untuk mengukur keberhasilan dan efektivitas edukasi dalam kegiatan pengabmas ini maka dilakukan evaluasi melalui pre-test dan post-test. Hasil kegiatan menunjukan terdapat 30 orang yang mengikuti kegiatan dan hasil post test menunjukkan bahwa setelah edukasi pengetahuan peserta naik sebesar 4,2 point (42%). Kesimpulan terdapat peningkatan pengetahuan masyarakat tentang penyakit hipertensi dan mampu membuat serbuk instan MORIZYA untuk pengendalian Hipertensi.